2013
DOI: 10.1097/aud.0b013e31828d269a
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Efficacy and Reliability of Training a Hearing Aid

Abstract: For those who wanted a change to the prescription, training was mostly effective. Limited data on reliability showed reasonable consistency in training outcomes and preferences. Findings, in particular on reliability, should be verified in larger populations. A guideline on how to clinically manage training with clients is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
(16 reference statements)
1
25
0
Order By: Relevance
“…The finding that about half of the participants who provided valid data reported no preference for either response is in agreement with the Keidser and Alamudi (2013) study. Zakis et al (2007) reported that only about one-quarter of participants had nonsignificant preferences.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The finding that about half of the participants who provided valid data reported no preference for either response is in agreement with the Keidser and Alamudi (2013) study. Zakis et al (2007) reported that only about one-quarter of participants had nonsignificant preferences.…”
Section: Discussionsupporting
confidence: 88%
“…One possible reason for this discrepancy is that participants in the present study completed an average of 142 training-phase listening evaluations over four weeks, fewer than the 300 adjustments required by Zakis et al Although no overall significant correlation between number of training-phase listening evaluations and preference for trained settings existed, among participants who completed more than 150 training-phase listening evaluations, 80% (4/5) had a significant preference for trained settings. Zakis et al (2007) and Keidser and Alamudi (2013) also found that training was effective for 75–80% of those participants who had trained the devices sufficiently across several environments.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Trainable hearing aids are an emerging technology that can enable the patient to manipulate amplification characteristics via user controls while wearing the hearing aid in real life. Over time, the hearing aid wearer's amplification preferences in different acoustic environments are "learned" by the hearing aid, which automatically adjusts its amplification parameters as the acoustics of the environment alter (Zakis et al, 2007;Keidser and Alamudi, 2013). Although studies evaluating the effectiveness of trainable hearing aids have shown higher patient preference for settings resulting from trained hearing aids compared to those prescribed in a clinic, further research regarding its reliability and the overall benefit that can be achieved are required (Zakis et al, 2007;Keidser and Alamudi, 2013).…”
Section: Lack Of Familiaritymentioning
confidence: 99%
“…Over time, the hearing aid wearer's amplification preferences in different acoustic environments are "learned" by the hearing aid, which automatically adjusts its amplification parameters as the acoustics of the environment alter (Zakis et al, 2007;Keidser and Alamudi, 2013). Although studies evaluating the effectiveness of trainable hearing aids have shown higher patient preference for settings resulting from trained hearing aids compared to those prescribed in a clinic, further research regarding its reliability and the overall benefit that can be achieved are required (Zakis et al, 2007;Keidser and Alamudi, 2013). Smartphone applications that enable users to program their hearing aids are now also available, although research evaluating this technology has not been carried out (Clark and Swanepoel, 2014).…”
Section: Lack Of Familiaritymentioning
confidence: 99%